The The Alleged Reference to the Tripartite Division of Jewish Law in 4QMMT - Klukowski, Michał Jarosław (The Biblical Annals, 2022)
The article discusses Elisha Qimron’s suggestion that the syntagm חוק ומשפט וטהרה (B 52 = 4Q394 8 IV,2; 4Q396 1–2 II,3-4) from 4QMMT indicated the tripartite division of Jewish law in the understanding of the Qumran community. The first part presents the context of the use of חוק ומשפט וטהרה in 4QMMT, and briefly analyses the use of each of these terms in the literature of the Second Temple Period. The second part raises arguments refuting E. Qimron’s idea and proposes an alternative meaning of חוק ומשפט וטהרה.